Students Perceptions of Mathematics Education on Online Learning at STKIP Tunas Palapa Central Lampung - Rini, Ambar Prisetia (Bulletin of Science Education, 2022)
The Covid-19 pandemic has brought major changes to the world, including in the field of education. In an effort to contain the spread of Covid-19, the Ministry of Education, Culture, Research, and Technology has made a policy regarding the online teaching and learning process. The article aimed to determine student perceptions of online learning during the Covid-19 pandemic. This research used a quantitative descriptive analysis method with research instruments in the form of questionnaires distributed online by using google forms. The number of samples in this study were 40 students of the Mathematics Education Study Program at STKIP Tunas Palapa that has been involved online learning during the Covid-19 pandemic. The results show that the majority of students agree more with offline learning in face-to-face classes than online learning. Constraints faced during online lectures make students want to renew the education system for the next lecture. The government needs to ensure the availability of adequate internet network access in all regions and campuses provide subsidized internet quota b for students. So that lecture activities going well and as expected for the learning process. Keywords: Students’ Perceptions, Mathematics Education, Online Learning